Degradation of AIF in mouse heart tissue for estimating postmortem interval (PMI). (December 2017) - Peng, Duo; Li, Zhilong; Tian, Huan; Chen, Dan; Wang, Jijun; Bai, Peng; Liang, Weibo; Zhang, Lin
Abstract: Estimating time of death in forensic routines is particularly important, and a range of time can be determined by traditional methods Degradation of mRNA has been used to estimate postmortem interval (PMI) and many potential mRNA markers are found in previous studies. In this study, we aimed to find a new mRNA marker which can determine PMI with its degradation. Besides, our previous results proposed that DNA was suitable as normalization. So, in this study we determined apoptosis inducing factor (AIF) degradation against Caspase-3 DNA to see if AIF is an effective marker to estimate time of death. To do that, corpses of mice in 37 °C were simulating the environment of summer days in Chengdu and heart tissue was obtained in different time points. RNA and DNA were co-extracted with Bioteke co-extraction kits followed by expression level detection with RT-qPCR of MiScript SYBR Green PCR Kit. The results showed that AIF was slowly degraded in 48 h PMI. What's more, AIF represented a faster degradation process and a good liner correlation within 14–20 h PMI. Therefore, we suggested AIF was an useful marker to estimate time of death in14–20 h PMI.